Study of the system of the witness appearing in court: From the perspective of criminal proceedings - Shanshan Zhao (Wolters Kluwer Medknow Publications, 2017)
It is of great significance for witnesses to appear in court in criminal cases so as to safeguard the right of confrontation of the defendant and achieve judicial justice. However, the witnesses in criminal cases refuse to appear in court and only give written testimony, and this has become a long-standing problem in the judicial practice of China. To solve this problem, the Criminal Procedure Law of China, amended and improved the system of the witness appearing in court in 2012. Nevertheless, if the underlying problems in the judicial system of China are not settled, the system of the witness appearing in court in criminal cases still cannot turn into practicable measures.